Reconnaissance des parcours individuels dans une méthodologie de groupe - Sophie Dufour; Chantal Parpette (Recherches en didactique des langues et des cultures)
Adult learners who decide to enroll in a French as a Foreign Language Course in France bring with them their projects, their work habits and their tastes, factors which contribute to the diversity of the class. The communicative methodology, with its notion of needs analysis, and particularly that of learner-centeredness, corresponds in theory to this reality. But it also enters into conflict with the conditions of teaching to groups in an institutional setting. The field study presented in this article focuses on the interface between a class grouping and a particular pupil, between the classroom setting and the surrounding environment. Its objective is to integrate into group methodology a consideration of the individual profiles of the learners.